2016
DOI: 10.1103/physrevlett.117.196802
|View full text |Cite
|
Sign up to set email alerts
|

Artificially Constructed Plasmarons and Plasmon-Exciton Molecules in 2D Metals

Abstract: Resonant optical excitation was used to create a macroscopic nonequilibrium ensemble of "dark" excitons with an unprecedented long lifetime in a two-dimensional electron system placed in a quantizing magnetic field. Exotic three-particle and four-particle states, plasmarons and plasmon-exciton molecules, coupled with the surrounding electrons through the collective plasma oscillations are engineered. Plasmarons and plasmon-exciton molecules are manifested as new features in the recombination spectra of nonequi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…In conclusion, we present the key results of this study. Further studies have been made to determine the properties of three-particle complexes discovered in [ 16 ]. It is experimentally shown that the PL spectrum of the 2D system in the quantum Hall insulator reveals new lines linked to the formation of a nonequilibrium triplet magnetoexciton ensemble.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we present the key results of this study. Further studies have been made to determine the properties of three-particle complexes discovered in [ 16 ]. It is experimentally shown that the PL spectrum of the 2D system in the quantum Hall insulator reveals new lines linked to the formation of a nonequilibrium triplet magnetoexciton ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…In a quantum Hall insulator at ν = 2, a photoexcited hole may occur in magnetoexciton-free space. Such a situation is easily realizable at temperatures above 1.5 K when practically all magnetoexcitons are "ionized" (relaxed to the ground state by the resonant conversion of the magnetoexciton into a magnetoplasmon and recombination of the latter) 16 . In this case, the recombination process involving the photoexcited hole becomes essentially singleparticle recombination.…”
Section: Trionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a relaxation process is impossible, for instance, at integer filling factor ν = 2, which reflects the incompressibility of the electron gas in the lowest energy spin sublevel of Landau level. This also leads to the formation of charged three-particle complexes (plasmarons and trions) [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the charge and spin dynamics in condensed matter is essential for the development of novel spintronic devices in which the combination of charge transport with ultrafast spin initialization using optical pulses can be exploited [1][2][3][4][5]. In semiconductors, conduction band electrons which are localized on donor atoms or potential fluctuations, demonstrate long spin relaxation times due to suppression of spin-orbit effects [6].…”
mentioning
confidence: 99%